Effect of different cure systems on natural rubber/nanocellulose nanocomposites in rheological, physical-mechanical, aging, and mechanical properties. (August 2022) - Honorato, Luciana Ribeiro; Visconte, Leila Lea Yuan; Nunes, Regina Célia Reis
The effect of different crosslink structures was studied in nanocomposites obtained by co-precipitation of natural rubber (NR) latex and aqueous solution of cellulose xanthate for obtaining nanocellulose. Cure systems characterized as conventional (CV), semi-efficient (SEV), and efficient (EV) were used in compositions of NR and also in natural rubber/cellulose (NR/CEL) nanocompositions with 15 phr of cellulose. The characterization of the developed compositions was based on rheological, physical-mechanical, aging, and mechanical properties. The obtained results allowed the conclusion that cellulose is a reinforcing filler as it promoted a significant increase in all these properties, that were sensitive to the cure systems used and protects NR from accelerated aging. The experimental results are presented and discussed also by Payne effect, entropy (ΔS), and Gibbs free energy (ΔG) to enable an understanding on cellulose distribution throughout NR influenced by the different cure systems.